EVOLUTION AND DEVELOPMENT OF MUSEUM EXHIBITION DISPLAY: HISTORICAL AND CULTURAL APPROACH - Tetiana Behal (Культура і мистецтво у сучасному світі, 2020)
The purpose of the article is to explore and reveal the nature of the museum display by progress analysis of its structures through the historical and cultural uplift of humankind. We have used the method of analysis and synthesis to obtain effective results. Through the progress analysis of the individual structures, it is established that the museum display is the result of the evolution and constant transformation of the historical, political, and cultural environment. The synthesis method allowed us to consider the museum display cohesiveness of the separate items and determine its value for the formation of the overall modern cultural space. The scientific novelty of the results lies in the fact that for the first time the nature of the museum display as a separate phenomenon was revealed. We have retraced the historical origins and directions of its development in the digital era. Conclusions. According to the stated aim, we have found out that a museum exhibition display has passed a long way of its development. Since the collections of Ancient Greek temples, and the brilliant collections of Roman patricians, the exhibition has acquired some forms (a gallery, a cabinet, an antiquarium, a studiolo) and signs of the Renaissance concept-based public object and exhibition space, the Enlightenment academic environment and the Romantic national identity, which is actively turning into a virtual environment within the digital era. The main factors of influence on overall development and advancement of the museum displays are analysed.